The Oxford companion to American literature - Hart, James D. (James David), 1911-1990.; Leininger, Phillip, 1928- (New York : Oxford University Press, 1995)
For the sixth edition, James D. Hart and Phillip Leininger have updated the Companion in light of what has happened in American literature since 1982. To this end, they have revised the entries on such established authors as Saul Bellow, Norman Mailer, and Joyce Carol Oates, and they have added more than 180 new entries on novelists (T. Coraghessan Boyle, Tim O'Brien, Louise Erdrich, Don De Lillo), poets (Rita Dove, Weldon Kees), playwrights (Wendy Wasserstein, August Wilson), popular writers (Stephen King, Louis L'Amour), historians (James M. McPherson, David Herbert Donald, William Manchester), naturalists (Aldo Leopold, Edward Abbey), and literary critics (Camille Paglia, Richard Ellmann). In addition, the Companion boasts more women's, African-American, and ethnic voices, with new entries on such luminaries as Charlotte Perkins Gilman, M. F. K. Fisher, William Least Heat-Moon, Ursula Le Guin, and Oscar Hijuelos, among many others. With over 5,000 total entries, The Oxford Companion to American Literature reflects a dynamic balance between past and contemporary literature, surveying virtually every aspect of our national literature, from the Pulitzer Prize to pulp fiction, and from Walt Whitman to William F. Buckley, Jr. There are over 2,000 biographical profiles of important American authors (with information regarding their styles, subjects, and major works) and influential foreign writers as well as other figures who have been important in the nation's social and cultural history. There are more than 1,100 full summaries of important American novels, stories, essays, poems (with verse form noted), plays, biographies and autobiographies, tracts, narratives, and histories. The new edition provides historical background and astute commentary on literary schools and movements, literary awards, magazines, newspapers, and a wide variety of other matters directly related to writing in America. Finally, the book is thoroughly cross-referenced and features an extensive and fully updated index of literary and social history.
Includes index.
Available also online via the Internet.
Keywords: American literature -- Dictionaries; American literature -- Bio-bibliography.; Authors, American -- Biography -- Dictionaries; American literature; Authors, American; Bio-bibliography.; Biography -- Dictionaries; Dictionaries